The heparin‐von Willebrand factor interaction and conventional tests of haemostasis – the challenges in predicting bleeding in cardiopulmonary bypass. (5th December 2020) - Ranger, Amita; Gaspar, Mihaela; Elkhatteb, Amira; Jackson, Tim; Fox, Steve; Aw, T. C.; Vipond, Lisa; Cotterill, Judy; Ghori, Arshad; Laffan, Mike; Arachchillage, Deepa R. J.
Summary: Bleeding is a significant complication of cardiopulmonary bypass (CPB), despite routine anticoagulation monitoring. This is likely to be multifactorial. In this prospective, single‐centre cohort study of 30 patients undergoing CPB surgery, our aim was to characterise the changes in von Willebrand factor (VWF) function, platelet interaction and the global coagulation changes during and after CPB surgery and to determine whether bleeding can be predicted. Samples were taken at six time points before, during and after CPB surgery. We observed a significant rise in VWF antigen (VWF:Ag) throughout surgery, which continued postoperatively. The absolute VWF collagen‐binding assays (VWF:CB) and VWF ristocetin cofactor (VWF:RCo) rose significantly but the VWF:CB/VWF:Ag and VWF:Ag/VWF:RCo fell significantly ( P = 0·0015 and P = 0·0143), suggesting loss of large multimers. We detected a non‐significant trend to loss of VWF:RCo after heparinisation and a significant recovery after protamine reversal which could reflect a direct heparin effect. There was a significant increase in the R and K times with a fall in alpha angle and maximum amplitude after heparin administration, using heparinase‐thromboelastography (TEG). The parameters both significantly improved following protamine ( P = 0·007 and P = 0·0054). The activated clotting time (ACT) and heparin anti‐Xa level correlated poorly; neither predicted clinically significant bleeding. None of these parameters had a relationship with intraoperative blood loss or requirement for blood product replacement.